Effects of anabolic steroids on the muscle cells of strength-trained athletes - Kadi, F.; Eriksson, A.; Holmner, S.; Thornell, L. E. (Medicine & Science in Sports & Exercise, 1999)
Purpose: Athletes who use anabolic steroids get larger and stronger muscles. How this is reflected at the level of the muscle fibers has not yet been established and was the topic of this investigation. Methods: Muscle biopsies were obtained from the trapezius muscles of high-level power lifters who have reported the use of anabolic steroids in high doses for several years and from high-level power lifters who have never used these drugs. Enzyme-immunohistochemical investigation was performed to assess muscle fiber types, fiber area, myonuclear number, frequency of satellite cells, and fibers expressing developmental protein isoforms. Results: The overall muscle fiber composition was the same in both groups. The mean area for each fiber type in the reported steroid users was larger than that in the nonsteroid users (P < 0.05). The number of myonuclei and the proportion of central nuclei were also significantly higher in the reported steroid users (P < 0.05). Likewise, the frequency of fibers expressing developmental protein isoforms was significantly higher in the reported steroid users group (P < 0.05). Conclusion: Intake of anabolic steroids and strength-training induce an increase in muscle size by both hypertrophy and the formation of new muscle fibers. We propose that activation of satellite cells is a key process and is enhanced by the steroid use. The incorporation of the satellite cells into preexisting fibers to maintain a constant nuclear to cytoplasmic ratio seems to be a fundamental mechanism for muscle fiber growth. Although all the subjects in this study have the same level of performance, the possibility of genetic differences between the two groups cannot be completely excluded.